2016
DOI: 10.5604/12321966.1203903
|View full text |Cite
|
Sign up to set email alerts
|

Pro-health behaviours – a sense of coherence as the key to a healthy lifestyle in rural areas?

Abstract: Background. Health-related behaviours and lifestyle are related to the salutogenic concept of health, whereas the major public health problems faced in rural areas include difficulties in encouraging people to a healthy lifestyle. Objective. The aim of the study is to explore mutual relationships between psychosocial-demographic factors and a sense of coherence. Material and method. Two-stage sampling was applied. Data were collected with the use of the Juczynski Health Behaviours Inventory and Antonovsky's SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
(21 reference statements)
2
11
0
3
Order By: Relevance
“…Respecting to treatment category, two studies 24,25 showed that people with a strong SOC have healthier behaviors and are more likely to change their LS. These results are consistent with studies that have stressed the importance of SOC in the dietary choices of people, therefore concluding that people with a strong SOC make healthier dietary choices, do more physical activity and have a lower alcohol and tobacco consumption [48][49][50][51][52] , as well as a lower BMI 53 . There were no studies that related SOC with pharmaceutical treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Respecting to treatment category, two studies 24,25 showed that people with a strong SOC have healthier behaviors and are more likely to change their LS. These results are consistent with studies that have stressed the importance of SOC in the dietary choices of people, therefore concluding that people with a strong SOC make healthier dietary choices, do more physical activity and have a lower alcohol and tobacco consumption [48][49][50][51][52] , as well as a lower BMI 53 . There were no studies that related SOC with pharmaceutical treatment.…”
Section: Discussionsupporting
confidence: 91%
“…A research carried out in 2016 regarding the lifestyle and pro-health behaviours on the rural areas of Subcarpathian region among 800 farmers aged 3060 indicated that almost a half of the questioned (47%) displayed a low level of pro-health behaviours. Similarly to the case of the examined doctors, women showed a higher level of pro-health behaviours than men (p < 0.001) (Binkowska-Bury et al, 2016). Also, the lifestyle of teachers, the vocational group who participate directly in shaping pro-health behaviours and attitudes, significantly stands out from the pro-health model (Prażmowska, Dziubak, Morawska, Stach, 2011;Laudańska-Krzemińska, 2014).…”
Section: Discussionmentioning
confidence: 70%
“…Nesta revisão, entende--se por promoção da saúde o processo de capacitação de indivíduos e coletividades para atuar na melhoria da qualidade de vida e da saúde 34 . Ao se considerar a promoção da saúde, observou-se que o conteúdo dos estudos abordou o desenvolvimento de habilidades pessoais, com ênfase na educação em saúde 11,12,14,21,26 . Nestes, a Teoria Salutogênica busca compreender as potencialidades das pessoas para se manterem saudáveis.…”
Section: Recursos Salutogênicos Para a Promoção Da Saúdeunclassified
“…Em relação ao senso de coerência e os recursos generalizados de resistência, oito publicações 11,13,15,18,21,23,26,28 descrevem que tais recursos servem para reforçar tal senso e mobilizar os indivíduos no processo de enfrentamento das adversidades, o que pode implicar resultados mais favoráveis em termos de saúde. Além disso, os recursos generalizados contribuem para melhorar o estilo de vida e a qualidade de vida das pessoas 14,16,19 .…”
Section: O Senso De Coerência Na Promoção Da Saúdeunclassified